مكافحة الإرهاب البحري في الاتفاقيات الدولية والقانون الجنائي الإمارات - سعيد سالم خليفة سالم المزروعي
Maritime terrorism is an emerging crime that can be distinguished from crimes that affect the safety of maritime navigation, such as piracy at sea, armed robbery against ships, and hijacking while flying over the high seas. This study aims to identify the concept of maritime terrorism and its risks, clarify the mechanisms of cooperation at international and regional levels in combating it, and highlight the role of the international and national judiciary in prosecuting the perpetrators of these crimes. It also reviews the efforts of the UAE in its fight against terrorism by emphasizing the importance of showing the different forms of maritime terrorism and its great progress and strengthening mechanisms of international and regional cooperation between countries to combat maritime terrorism in all its forms. The statement of problem highlights that despite the multiplicity of international conventions related to combating the crimes of maritime terrorism, they have not been able to eradicate this phenomenon. Thus, this requires reviewing, developing, and updating national laws to reduce the commission of illegal acts directed against the safety of maritime navigation and help in preventing it, draining its sources, and punishing the perpetrators. A variety of scientific approaches were employed in this study, such as the descriptive approach, the analytical approach, the deductive approach, and the historical approach with the aim of describing the problem and its legal dimensions and analysing it according to the rules of criminal law, the treaty on maritime terrorism and national legislation. The study also emphasized the role of International and national laws in bringing those responsible for these crimes to criminal justice and evaluating the efforts of the UAE in combating maritime terrorism in all its aspects. The study reached various findings, the most important of which is that maritime terrorism is an international crime that falls within the jurisdiction of international criminal law and is not an ordinary crime that falls within the jurisdiction of a state. Among the important recommendations in the study, maritime terrorism as one of the most severe crimes requires international agreement on a common concept of maritime terrorism applicable to the competent national and international courts, there is also a need to define a unified concept of maritime terrorism that enjoys international consensus, making accountability based on controls of clear and specific laws, in accordance with the principle of legality of crimes and penalties, in order to address the concerns of maritime terrorism that affect maritime navigation and hold those responsible accountable and be subjected to crimes of maritime terrorism under the jurisdiction of the International Criminal Court. Finally, the study recommended that the UAE criminal legislator initiate an update of the existing criminal laws and the introduction of legal provisions criminalizing maritime terrorism, taking into account the legal standards as recommended by the legal commission on international navigation.